The Process of Solving the Problem of Being a Character and Being on the Character’s Objective: a Case Study of the Character “MASHA” in Christopher Durang’s Vanya and Sonia and Masha and Spike (2012) - Senwirach, Nawachat (Siam Communication Review, 2025)
This research article explores the process of solving the problems of being a characterization and being on a character’s objective : A case study of the character "Masha" in the play Vanya and Sonia and Masha and Spike (2012) by Christopher Durang. The objectives are to practice and develop the actor’s skills in characterization and living the character's needs, and to discover approaches to resolving these the problems of being a characterization and being on a character’s objective of the character "Masha." Due to the researcher's limited acting experience, they encountered two primary challenges 1.) the problems of being a characterization or getting into the character and 2.) being on a character’s objective with the research question focuses on how the researcher can enhance their skills in characterization and being on a character’s objective when performing in the play Vanya and Sonia and Masha and Spike. The study involves reviewing the theories and methods of Western theater practitioners learned in the Master's program at the Department of Dramatic Arts, Faculty of Arts, Chulalongkorn University. The proposition suggests that understanding and the process of solving the problems of being a characterization and being on a character’s objective "Masha" will enable the researcher's body to respond naturally as an actor. The research is divided into four phases: 1.) script and character analysis 2.) rehearsal process 3.) pre-production and 4.) production and post-production. The research utilizes two tools for evaluation 1.) video recordings and observations of rehearsals, including notes from the director after each rehearsal, and 2.) post-performance evaluations through questionnaires from audience, feedback from the director, and from the acting advisor. The findings indicate that effective the problems of being a characterization and being on a character’s objective start with understanding the character's mindset and emotions. By remaining present in the moment, the researcher can communicate the role effectively, adapt various acting methods, and perform appropriately according to the scene's context. The study integrates the acting concepts, theories, and techniques of three renowned acting experts: 1.) Sanford Meisner 2.) Konstantin Stanislavski and 3.) Lee Strasberg.Despite their differing principles, all three share the same goal to help actors create realistic and vibrant performances by deeply connecting with the character's emotions, thoughts and behaviors to establish credibility in acting